2009
DOI: 10.1001/archdermatol.2009.84
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous T-Cell Lymphoma Localized to the Lower Leg

Abstract: Background: Distinct categories of skin lymphoma with preferential site localization and unique clinical behavior, including leg-type primary cutaneous diffuse large B-cell lymphoma, have recently been described. Although these entities are rare, they exhibit reproducible clinicopathologic features, and their recognition may allow more appropriate treatment protocols.Observations: We describe the distinctive clinicopathologic features that were observed in 3 patients with an unusual variant of primary cutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…6 More recently, an atypical presentation of a faint erythematous eruption was described by a group from Japan. 7 Our series was similar to larger collaborative studies in many findings, including male predominance, mean age of 71.2 years, duration between skin manifestations and diagnosis, treatment choice of systemic anthracyclinecontaining chemotherapy for late stage disease, and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 More recently, an atypical presentation of a faint erythematous eruption was described by a group from Japan. 7 Our series was similar to larger collaborative studies in many findings, including male predominance, mean age of 71.2 years, duration between skin manifestations and diagnosis, treatment choice of systemic anthracyclinecontaining chemotherapy for late stage disease, and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, primary cutaneous ALCL has a favorable prognosis with a 10-year overall survival rate of 90% [ 15 ]. However, studies have shown that patients with lesions located in the upper and lower extremities have a worse prognosis [ 16 , 17 ]. Primary cutaneous ALCL can affect immunosuppressed individuals, including those with human immunodeficiency virus (HIV) infection, status post organ transplantation, or those treated with immunomodulatory drugs, such as adalimumab (tumor necrosis factor inhibitor), which is used to treat patients with autoimmune disorders, or fingolimod, which is used to treat patients with relapsing–remitting multiple sclerosis [ 17 , 18 , 19 ].…”
Section: Clinical Presentationmentioning
confidence: 99%